Effect of Nitrates supplementation on Muscle Hypertrophy and Athletic Performance: A Narrative Review - Stefanska, Olga; Rudnicki, Jakub; Szczepocki, Matthew; Jurek, Joanna Michalina (Tanjungpura Journal of Coaching Research, 2024)
Background and Study Aim. The consumption of nitrate has been linked to various advantages, including aiding recovery by lessening fatigue, enhancing oxygen supply to muscles, and increasing the elimination of metabolic by-products during intense physical activity. Given the rising trend of utilizing dietary supplements for peak athletic performance, this literature review aims to explore the role and promise of nitrate supplementation in influencing muscle function and boosting physical prowess, while also shedding light on its potential perks and drawbacks.Material and Methods. Electronic databases including Web of Science (all databases), PubMed, Scopus, Google Scholar, Science Direct, were explored on June 11, 2022. The search terms were drawn from prior systematic reviews on nitrate supplementation and exercise and informed by a recent narrative review on Nitrates impact on athletic performance and muscle hypertrophy.Results. The findings of this review indicate that nitrate intake, owing to its ability to widen blood vessels, could potentially enhance blood flow and oxygen delivery to muscles during exercise. Consequently, this improved circulation might facilitate better nutrient and oxygen transportation to muscle tissue, thereby fostering muscle development through enhanced nutrient absorption and waste removal during physical exertion. However, it's crucial to note that excessive nitrate consumption might trigger adverse effects related to the formation of nitrosamines.Conclusion. In summary, investigations into the potential advantages of nitrate supplementation, whether through dietary sources or supplements, in augmenting athletic performance are promising. This is evident from the observed effects of increased muscle protein synthesis, reduced muscle soreness, and enhanced cognitive function under stressful conditions. Nonetheless, it's imperative to exercise caution against over-supplementation due to the potential risks of toxicity and associated side effects.